PUBLIC POLICY INCIDENCE TOWARDS APPROPRIATE PHYSICAL EDUCATION (Fiep Bulletin - online, 2020)
Public policies are considered government actions with public interest objectives, which supplement all the need of citizens in the solution of social problems, giving us the possibility of generating various strategies to improve the education of physical education from early childhood strengthening aspects of human development. Its impact on the social and cultural environment of the peoples evidences that it is necessary to implement it through a serious policy that encapsulates physical, economic and intellectual resources, guaranteeing a greater well-being of the youth, having a positive impact on the whole society. This fact is made possible by creating mechanisms for the preparation of our students, raising awareness of the importance of good health, which has given better long-term results for everyone. And as a beginning, this process must be taken into account, from the schools providing an integral education, without excluding training areas, without decreasing their hourly intensity, let alone detract from the importance of human development. In almost all the countries of South America this situation occurs with the area of ??physical education. Because not follow good examples of public policies towards the teaching of physical education such as Canada, Spain, China, Finland, Germany, who begin their processes at an early age. The problem raised is the appropriate teaching of physical education in preschool and primary school in public institutions, considering these levels as fundamental in the integral education of the student. representing a factor that makes it impossible to guarantee a quality education.
Keywords: Public policies; physical education